Analisis Kemampuan Berpikir Kritis Matematika Siswa Ditinjau Dari Gaya Belajar Siswa - Elfiandi Rizaldi; Fauziah Anugrah; Nisvi Sya’bania Octiani; Puji Febriana Islamia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims to analyze students’ critical thinking abilities based on learning styles. This research uses qualitative research methods. This research began by giving tests to class IX-A students to obtain data on students' mathematical critical thinking abilities. The results of this research show that only 14% of students were able to achieve the KKM score, while 86% failed to achieve it. This shows that students' critical thinking skills are highly valued in mathematics education. The conclusion of this research is that students' critical thinking abilities in terms of learning styles in quadratic function material are still relatively low.